EFFICACY OF HERBAL METHIONINE (NUTRI-METHIONINE) SUPPLEMENTATION WITH SYNTHETIC DL-METHIONINE ON GROWTH OF BROILER CHICKEN (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted to evaluate the efficacy of herbal Methionine (Nutri Methionine) and synthetic DL- Methionine supplementation on the performance of broiler chicken. One hundred thirty five day old broiler chicks were divided into three groups with three replicates having fifteen chicks in each replicate. T1 group birds were fed with the control diet without any supplemental Methionine. T2 group birds were fed diet supplemented with synthetic DL- Methionine and T3 group were fed with diet supplemented with herbal Methionine. Results indicated that the body weight gain was significantly (P
Keywords: Broiler Chicken; Performance; Synthetic & Herbal Methionine